THE IMPACT OF ETHICAL ENVIRONMENT ON BUDGET GAMING BEHAVIOUR - Tin, Se; Setiawan, Santy; Christy, Yunita; Debbianita, Debbianita; En, Tan Kwang (2021)
Budget gaming behavior has been a concern in the organization for a long time and this dysfunctional behavior is often associated with ethics. This study examines perceptions of the ethical environment and trust as a potential determinant of budget gaming behavior. A survey questionnaire was used to collect data. The sample was drawn from 112 managers in go public manufacturing companies in Indonesia to determine if perceptions of the ethical environment and trust are determinants of budget gaming behavior. The data were analyzed by partial least square. The results indicate that the ethical environment has a positive effect on trust; trust negatively affects the budget gaming behavior; trust significantly mediates the relationship between ethical environment and budget gaming behavior. This study provides a warning for companies to truly concern about the ethical environment because its impact on dysfunctional behavior that causes serious harm to the organization.